2005
DOI: 10.1212/01.wnl.0000167544.54228.95
|View full text |Cite
|
Sign up to set email alerts
|

Generalized atherosclerosis, cognitive decline, and depressive symptoms in old age

Abstract: In the population at large, generalized atherosclerosis contributes to cognitive decline in old age but not to depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
57
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 49 publications
11
57
1
3
Order By: Relevance
“…The associations between lower cognitive function and macrovascular disease were not specific for the diabetic group. Similar associations have been shown for the whole Leiden 85-plus population [19]. The repeated analysis of the association between diabetes and cognition while adjusting for the presence of macrovascular disease (myocardial infarction, arterial surgery, intermittent claudication, or stroke) showed a 5-10% reduction in the estimates of the difference between diabetic and non-diabetic participants, as presented in …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The associations between lower cognitive function and macrovascular disease were not specific for the diabetic group. Similar associations have been shown for the whole Leiden 85-plus population [19]. The repeated analysis of the association between diabetes and cognition while adjusting for the presence of macrovascular disease (myocardial infarction, arterial surgery, intermittent claudication, or stroke) showed a 5-10% reduction in the estimates of the difference between diabetic and non-diabetic participants, as presented in …”
Section: Resultssupporting
confidence: 77%
“…In our study, worse cognitive performance in the diabetes group was associated with macrovascular disease. However, this association did not appear to be specific for diabetes [19] and adjustment for macrovascular disease in the analyses had only a modest effect on the difference in cognitive performance between diabetic and non-diabetic participants. While hypertension has been suggested to be an important determinant of impaired cognition in diabetes [4], in the present study no clear relationship was found between hypertension and cognitive function within the group of diabetes patients, in line with other recent studies [27,29].…”
Section: Discussionmentioning
confidence: 75%
“…Cardiovascular diseases, such as myocardial infarction, generalized atherosclerosis, and stroke have been associated with increased dementia risk and cognitive decline. [1][2][3][4] Hypertension, however, is only a risk factor for dementia when present in middle age, whereas most studies show that dementia and cognitive decline in the oldest old associate with lower blood pressures. 5 In the oldest old, blood pressures decrease over time, 6,7 and stronger declines are related to the presence of dementia and cognitive decline.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of exercise capacity associated with mildly compromised cognitive performance was only partially explained by a positive history of previous cerebrovascular disease, which has been demonstrated to influence both cognitive function (36) and exercise tolerance (37).…”
Section: © 2 0 1 0 E D I T R I C E K U R T I S F O R P E R S O N Amentioning
confidence: 98%